Developmental outcome of extremely preterm infants is improved after less invasive surfactant application: Developmental outcome after LISA. (25th September 2020) - Mehler, Katrin; Broer, Alexander; Roll, Claudia; Göpel, Wolfgang; Wieg, Christian; Jahn, Peter; Teig, Norbert; Höhn, Thomas; Welzing, Lars; Vochem, Matthias; Hoppenz, Marc; Bührer, Christoph; et al.
Abstract: Aim: The aim of this study was to evaluate neurocognitive outcome at 24 months of corrected age after less invasive surfactant application (LISA) in preterm infants born at 23‐26 weeks of gestational age. Methods: Surviving participants of a LISA trial conducted in 13 German level III neonatal intensive care units were reviewed for assessment of developmental outcome, hearing and vision problems, growth and rehospitalisation days. Maternal depression, breastfeeding rates and socio‐economic factors were evaluated as potentially confounding factors. Results: In total, 156/182 infants took part in the study, 78 had received surfactant via LISA and 78 via endotracheal intubation. 22% of LISA infants compared to 42% of intubated infants had a psychomotor development index (PDI) <70 (0.012). A significant difference in mental development index (MDI) was observed in the stratum of more mature infants (25 and 26 weeks of GA). For this group, MDI < 70 was observed in 4% of LISA infants vs 21% of intubated infants ( P  = 0.008). Conclusion: At 24 months of age, the LISA‐treated infants scored less often PDI < 70 and had similar results in MDI. Infants born at 25 and 26 weeks treated with LISA had lower rates of severe disability. LISA is safe and may be superior.